PTU-087 A specialised IBD service provides equality of access to healthcare, irrespective of deprivation indices. (8th June 2018) - Burkitt, Michael; Storey, Daniel; Gregg, Belle; Probert, Chris; Sawbridge, David
Abstract : Introduction: The Merseyside region is amongst the most deprived in the UK. The association between deprivation and poor healthcare outcomes is well-established. Many factors combine to influence this, including having poorer access to healthcare services. The Royal Liverpool and Broadgreen University Hospitals NHS Trust (RLBUHT) provides a regional referral service for patients with complex inflammatory bowel diseases (IBD), and secondary care IBD services for its local area. We investigated whether the IBD clinic patients reflect the city's deprivation, and analysed whether access to clinician time, and provision of high-cost biologic medicines was equitable. Methods: Records of consultations from IBD clinics were obtained for the period 11/09/2014–20/10/2017. Data were linked to a departmental database of biologic prescribing and full-postcode English Indices of Multiple Deprivations 2015. In addition to published national deciles of multiple deprivations, deciles of deprivation within the Liverpool postcode area were generated. Results: Data were collected for 3526 patients, and 15 219 consultations. As expected, Liverpool was shown to be highly deprived: 32% of postcodes within the Liverpool area postcode were in the lowest national decile of deprivation ( χ 2 p<0.001). Similarly, 40% of patients attending IBD clinic live at addresses in the most deprived decile nationally ( χ 2 p<0.001).Due to the skew towards deprived patients, national deprivation indices have limited value in assessing access to services in Liverpool. By plotting the deprivation of patients based on a specific Liverpool deprivation index we demonstrated a more even distribution of patients, although the most deprived group remained overrepresented ( χ 2 p<0.001). The distribution of IBD patients was similar to that observed for patients with irritable bowel syndrome managed within the trust, suggesting that this is a true representation of the patient cohort served by the organisationPatients accessed clinics with similar frequency whatever their deprivation status (Kruskall-Wallis 1-way ANOVA p=0.5215). Patients' access to biologic agents was similar across Liverpool deprivation deciles ( χ 2 p=0.058). Conclusions: The IBD patient cohort managed at RLBUHT is highly deprived, even with respect to the surrounding city. Patients managed within the service have similar access to clinicians and high-cost treatment irrespective of deprivation. Whilst this study has not identified inequity of access to services, to confidently exclude this, further studies integrating primary and secondary care datasets are needed.